2017
DOI: 10.1186/s12957-016-1091-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and prognostic factors for gastric cancer patients with bone metastasis

Abstract: BackgroundBone metastasis due to gastric cancer is rare, and the clinical features have not been fully evaluated. We investigated the clinical features, treatment outcomes, and prognostic factors in gastric cancer patients with bone metastasis.MethodsWe retrospectively collected data on 34 consecutive patients who were diagnosed radiologically with bone metastasis due to gastric cancer. We estimated the overall survival after the diagnosis of bone metastasis using the Kaplan-Meier product-limit method and eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 16 publications
2
28
0
Order By: Relevance
“…The metastatic rate to above four sites were much higher than previous literature reports, which were 13.5% for liver metastasis,15 0.5%‐0.96% for lung metastasis,16, 17, 18 0.9%‐3.8% for bone metastasis19, 20, 21, 22 and 0.16%‐0.69% for brain metastasis 23, 24. The actual frequency of metastasis to bone and brain originating from GC was underestimated because usually bone and brain imaging was not performed as a routine evaluation and asymptomatic metastasis might be overlooked 25, 26. In our study, we found that the frequency of bone metastasis was similar to lung metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The metastatic rate to above four sites were much higher than previous literature reports, which were 13.5% for liver metastasis,15 0.5%‐0.96% for lung metastasis,16, 17, 18 0.9%‐3.8% for bone metastasis19, 20, 21, 22 and 0.16%‐0.69% for brain metastasis 23, 24. The actual frequency of metastasis to bone and brain originating from GC was underestimated because usually bone and brain imaging was not performed as a routine evaluation and asymptomatic metastasis might be overlooked 25, 26. In our study, we found that the frequency of bone metastasis was similar to lung metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Imaging examinations like bone scan, MRI, or PET-CT were more appropriate compared to laboratory indexes like ALP, LDH, and tumor markers in some researches. [ 19,22] Thus, method and frequency of bone scan need to be estimated in further study.…”
Section: Discussionmentioning
confidence: 99%
“…Since there had not clear guideline for treatment of GCBM, some researches thought that chemotherapy and bisphosphonate therapy will improve overall survival and prolong time to the first SRE. [ 7,8,10,[17][18][19] Besides, radiotherapy may be quite effective to relieve severe pain and to prevent fractures in GCBM but with no improvement in survival. [ 8,10,20] However, the role of surgery in GCBM had not been identified yet.…”
Section: A Korean Research [mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the patients with invasion and metastasis have poorer prognosis. 4,5 Therefore, it is crucial to explore the molecular mechanism underlying the progression of GC.…”
Section: Introductionmentioning
confidence: 99%